Five new species in the predaceous midge genus Macrurohelea Ingram & Macfie from Argentina, and descriptions of the previously unknown males of M. kuscheli Wirth and M. monotheca Spinelli & Grogan (Diptera: Ceratopogonidae) - Spinelli, Gustavo R.; Ronderos, Maria M.; Grogan, William L. Jr. (Zootaxa, 2022)
Five new Neotropical species in the predaceous midge genus Macrurohelea Ingram & Macfie are described: M. bassoi, M. donatoi, M. morenoi, M. sirii, and M. ventanensis, n. spp. and the previously unknown males of M. kuscheli Wirth and M. monotheca Spinelli & Grogan are described from specimens collected in several localities of Argentina and Chile. Illustrations and photomicrographs of key features of both sexes are provided as well as a key to all Neotropical species of Macrurohelea.